HENRYKA KUPISZEWSKIEGO WIZJA PRAWA RZYMSKIEGO - Wołodkiewicz, Witold (Zeszyty Prawnicze, 2016)
Henryk Kupiszewski’s Vision of Roman Law Summary This article is an extended version of the author’s paper delivered at the International Conference held at the University of Warsaw to commemorate the twentieth anniversary of the death of Professor Henryk Kupiszewski. The author presents the biography and academic developments in the life of Kupiszewski, a student of Wacław Osuchowski, Rafał Taubenschlag, and Max Kaser. He then goes on to discuss Kupiszewski’s main research interests. Starting with papyrology for the legal sciences, Kupiszewski moved on to research on the internal history of classical Roman law and finally to the study of the impact of Roman law on contemporary law and legal culture. The author also recalls Kupiszewski’s work in international co-operation in scholarship and for the Polish diplomatic service as ambassador to the Vatican.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />